2001
DOI: 10.1103/physrevlett.87.256102
|View full text |Cite
|
Sign up to set email alerts
|

How Do Gold Nanowires Break?

Abstract: Suspended gold nanowires have recently been made in an ultrahigh vacuum and were imaged by electron microscopy. Using realistic molecular dynamics simulation, we study the mechanisms of formation, evolution, and breaking of these atomically thin Au nanowires under stress. We show how defects induce the formation of constrictions that eventually will form the one-atom chains. We find that these chains, before breaking, are five atoms long, which is in excellent agreement with experimental results. After the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
213
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(247 citation statements)
references
References 20 publications
(31 reference statements)
25
213
0
9
Order By: Relevance
“…With the strain up to 39.12%, those atoms at the 'tip' of the neck rearrange themselves into an one-atom thick, about three-atoms long necklace (see Fig. 5(b)) which is some similar to what happened in the gold nanowire [18,21]. However, this is not observed for Ni nanowire simulated by Sorensen et al [17].…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…With the strain up to 39.12%, those atoms at the 'tip' of the neck rearrange themselves into an one-atom thick, about three-atoms long necklace (see Fig. 5(b)) which is some similar to what happened in the gold nanowire [18,21]. However, this is not observed for Ni nanowire simulated by Sorensen et al [17].…”
Section: Resultsmentioning
confidence: 71%
“…However, measuring the mechanical and electrical properties of a nanowire is a difficult task due to the small dimensions [11]. In recent years, the deformation of nanowires have been studied by molecular dynamics simulations using either embodied-atom-method (EAM) [12][13][14][15] or effective-medium theory (EMT) [16,17] potentials as well as first-principles method based on the density functional theory (DFT) [18][19][20][21]. These studies focus on the correlation of the force (associated with the changes in the bonding of the nanowire) and the conductance for the metallic Au, Ni, and Na nano-contacts [17,22] and Au, Ni, Al, Na, and SiSe 2 nanowire [12,16,20,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the unique mechanical, thermal, electrical and optical properties, materials with nanometer-sized structure have attracted a great deal of interest as potential building blocks in nanoelectronic and nanoelectromechanical devices [1]. Many researchers have demonstrated, through both experiments and analysis, that the structure and properties of nanowires can be quite different from those of bulk materials due to the effect of the large surface to volume ratio [2][3][4][5][6][7][8][9][10][11][12][13][14].Recently, Uchic et al [15,16] and Greer et al [17,18] reported that the plastic deformation behavior of single-crystalline sub-micropillars is dependent on the size of the pillar, even without a deformation gradient. More recently, a ''mechanical annealing" test was used to demonstrate that dislocations can be swept out of the samples through the progressive activation and exhaustion of dislocation sources [19].…”
mentioning
confidence: 99%